Efficacy of 5% Minoxidil Versus Platelet Rich Plasma in Treatment of Alopecia Areata - Goraya, Saman Iqbal; Aamir, Safoora; Jabeen Bajwa, Beenish; Rahat, Beenish; Afzal, Tassmia; Naseem, Riffat (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the efficacy of 5% Minoxidil versus Platelet Rich Plasma in treatment of alopecia areata.Study Design: Quasi experimental study.Place and Duration of Study: Department of Dermatology, Sheikh Zayed Hospital, Lahore, Pakistan, from Apr to Sep 2022.Methodology: A total of 122 patients with alopecia areata, aged between 18-40 years and belonging to both genders, were enrolled after taking written, informed consent and were randomly and equally divided between two groups, of which, group A, received 5% Minoxidil, while group B, received intralesional Platelet Rich Plasma. Efficacy was assessed over 12 weeks in terms of improvement in Severity of Alopecia Tool (SALT) score.Results: The mean age of the patients in group A was 25.1±6.1 years while in group B, it was 26.3±5.0 years. The mean SALT score at baseline was 74.3±7.8 versus 73.0±6.8 (p=0.311), while the mean SALT score at 12 weeks was 37.3±9.6 versus 33.6±8.7 (p=0.029) respectively. Comparison of efficacy of Minoxidil versus Platelet Rich Plasma revealed that Minoxidil was effective in 33 patients (54.1%), whereas, Platelet Rich Plasma was effective in 46 patients (75.4%), with this difference being statistically significant (p-value ≤0.05).Conclusion: Platelet Rich Plasma was significantly more effective than Minoxidil in the treatment of patients presenting with alopecia areata.